2023
DOI: 10.3390/ijms24054434
|View full text |Cite
|
Sign up to set email alerts
|

Altered Differential Expression of Genes and microRNAs Related to Adhesion and Apoptosis Pathways in Patients with Different Phenotypes of Endometriosis

Abstract: We aim to investigate the expression of genes (MAPK1 and CAPN2) and microRNAs (miR-30a-5p, miR-7-5p, miR-143-3p, and miR-93-5p) involved in adhesion and apoptosis pathways in superficial peritoneal endometriosis (SE), deep infiltrating endometriosis (DE), and ovarian endometrioma (OE), and to evaluate whether these lesions share the same pathophysiological mechanisms. We used samples of SE (n = 10), DE (n = 10), and OE (n = 10), and endometrial biopsies of these respective patients affected with endometriosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 59 publications
0
5
0
Order By: Relevance
“…Furthermore, we linked these miRNAs to disease ( Table 1 ). The miRNAs miR-128-3p, miR-27a-3p, miR-27b-3p, miR-181a-5p, miR-181b-5p, miR-452-3p, miR-216a-5p, miR-216b-5p, and miR-93-5p are targets for future functional studies as they are related in endometriosis to diagnostic biomarkers [ 42 ], autophagy [ 43 ], and the regulation of inflammation, vascularization, and angiogenesis of the endometrium during the menstrual cycle and decidualization [ 44 ]; fibrosis modulation [ 45 ]; enhancement of cell proliferation, migration, and invasion [ 46 ]; expression influenced by E2 and BPA [ 44 ]; regulation of human endometrial stromal cell decidualization [ 55 ]; expression regulated by the menstrual cycle [ 42 ]; stromal cell invasion and migration [ 48 ]; expression exclusively in ectopic stromal cells [ 48 ]; and sustained cell proliferation, cellular adhesion, and apoptosis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, we linked these miRNAs to disease ( Table 1 ). The miRNAs miR-128-3p, miR-27a-3p, miR-27b-3p, miR-181a-5p, miR-181b-5p, miR-452-3p, miR-216a-5p, miR-216b-5p, and miR-93-5p are targets for future functional studies as they are related in endometriosis to diagnostic biomarkers [ 42 ], autophagy [ 43 ], and the regulation of inflammation, vascularization, and angiogenesis of the endometrium during the menstrual cycle and decidualization [ 44 ]; fibrosis modulation [ 45 ]; enhancement of cell proliferation, migration, and invasion [ 46 ]; expression influenced by E2 and BPA [ 44 ]; regulation of human endometrial stromal cell decidualization [ 55 ]; expression regulated by the menstrual cycle [ 42 ]; stromal cell invasion and migration [ 48 ]; expression exclusively in ectopic stromal cells [ 48 ]; and sustained cell proliferation, cellular adhesion, and apoptosis [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…Illustratively, a recent examination focusing on miRNAs governing adhesion and apoptosis revealed a noteworthy elevation in the expression levels of miR-93-5p and miR-7-5p in the cohorts afflicted with deep infiltrating endometriosis and endometrioma, as opposed to those presenting with lesions of superficial peritoneal endometriosis. Perhaps these results could help identify differences between pathological phenotypes of endometriosis [62].…”
Section: Apoptosis In Endometriosismentioning
confidence: 97%
“…Several studies have reported changes in the expression of specific miRNAs in endometriotic lesions. These miRNAs include miR-1, miR-29c, miR-34c, miR-100, miR-141, miR-145, miR-183, miR-196b, miR-200a, miR-200b, miR-200c, miR-202, miR-365, and miR-375 [142]. Some of these miRNAs are known to play roles in processes such as Epithelial-Mesenchymal Transition (EMT), angiogenesis, cell proliferation, cell adhesion, and invasion [142,143].…”
Section: The Pathological Role Of Mirnas In Endometriosismentioning
confidence: 99%
“…These miRNAs include miR-1, miR-29c, miR-34c, miR-100, miR-141, miR-145, miR-183, miR-196b, miR-200a, miR-200b, miR-200c, miR-202, miR-365, and miR-375 [142]. Some of these miRNAs are known to play roles in processes such as Epithelial-Mesenchymal Transition (EMT), angiogenesis, cell proliferation, cell adhesion, and invasion [142,143]. EMT and angiogenesis are crucial components of the pathophysiology of endometriotic lesion formation.…”
Section: The Pathological Role Of Mirnas In Endometriosismentioning
confidence: 99%